Electrophysiological In Vitro Study of Long‐Range Signal Transmission by Astrocytic Networks - Nataly Hastings; Yi‐Lin Yu; Botian Huang; Sagnik Middya; Misaki Inaoka; Nadia A. Erkamp; Roger J. Mason; Alejandro Carnicer‐Lombarte; Saifur Rahman; Tuomas P. J. Knowles; Manohar Bance; George G. Malliaras; et al. (Advanced Science, 2023)
Abstract Astrocytes are diverse brain cells that form large networks communicating via gap junctions and chemical transmitters. Despite recent advances, the functions of astrocytic networks in information processing in the brain are not fully understood. In culture, brain slices, and in vivo, astrocytes, and neurons grow in tight association, making it challenging to establish whether signals that spread within astrocytic networks communicate with neuronal groups at distant sites, or whether astrocytes solely respond to their local environments. A multi‐electrode array (MEA)‐based device called AstroMEA is designed to separate neuronal and astrocytic networks, thus allowing to study the transfer of chemical and/or electrical signals transmitted via astrocytic networks capable of changing neuronal electrical behavior. AstroMEA demonstrates that cortical astrocytic networks can induce a significant upregulation in the firing frequency of neurons in response to a theta‐burst charge‐balanced biphasic current stimulation (5 pulses of 100 Hz × 10 with 200 ms intervals, 2 s total duration) of a separate neuronal‐astrocytic group in the absence of direct neuronal contact. This result corroborates the view of astrocytic networks as a parallel mechanism of signal transmission in the brain that is separate from the neuronal connectome. Translationally, it highlights the importance of astrocytic network protection as a treatment target.